Apocynin exhibits an ameliorative effect on endothelial dysfunction/atherosclerosis-related factors in high-fat diet-induced obesity in rats - ERTAŞ, BÜŞRA; KOÇYİĞİT SEVİNÇ, SEVGİ; ERCAN, FERİHA; ORUN, OYA; AKKİPRİK, MUSTAFA; ÇETİNEL, ŞULE (My University, 2024)
Objective: The aim of this study was to reveal the effect of apocynin (APO) on the factors involved in obesity-related endothelial dysfunction (ED) and atherosclerosis (AS). Materials and Methods: Male Wistar albino rats were divided into control (CNT), high-fat diet (HFD) and HFD+APO groups. HFD and HFD+APO groups were fed HFD for sixteen weeks. APO (25 mg/kg) was administered to the HFD+APO group for the last four weeks. The effects of APO on: AS-related metabolic parameters (triglyceride, total cholesterol, high-density lipoprotein-cholesterol, insulin and leptin), oxidative stress (OS), [ malondialdehyde, glutathione, nicotinamide adenine dinucleotide phosphate (NADPH)-oxidase-2, oxidised-low-density lipoprotein (ox-LDL) and 8-hydroxy-2-deoxyguanosine], low-density lipoprotein and ox-LDL uptake potential (activin receptor-like kinase-1 and lectin-like oxidized low-density lipoprotein receptor-1, respectively), tissue inflammation (myeloperoxidase, monocyte-chemoattractant-protein-1, tumor necrosis factor-alpha), ED (endothelial-nitric oxide synthase, inducible-nitric oxide synthase, nitric oxide), programmed cell death (terminal deoxynucleotidyl-transferase-dUTP-nick-end labeling, cleaved-poly-ADP-ribose-polymerase, gasdermin-D N-terminal fragment, caspase-1), smooth muscle cell transformation (alpha-smooth muscle actin), histology and ultrastructure of thoracic aorta were evaluated. Results: In obesity, APO had an ameliorative effect on metabolic parameters, OS, inflammation, ED, programmed cell death and oxLDL uptake potential, but not on foam cell formation and LDL uptake potential. Conclusion: Apocynin may improve ED and AS in obesity by suppressing OS-linked factors involved in the early stage of AS.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Apocynin; Atherosclerosis; Endothelial dysfunction; High-fat diet; Obesity; Oxidative stress